Predictors of positive outcomes from ‘Early Intervention in Psychosis’: protocol for a national retrospective cohort study - Williams, Ryan; Penington, Ed; Gupta, Veenu; Tsiachristas, Apostolos; French, Paul; Lennox, Belinda; Bottle, Alex; Crawford, Mike J. (Frontiers in Psychiatry, 2023)
Psychotic disorders are severe and prevalent mental health conditions associated with long-term disability, reduced quality of life, and substantial economic costs. Early Intervention in Psychosis (EIP) services aim to provide timely and comprehensive treatment for psychotic disorders, and EIP service input is associated with improved outcomes. However, there is limited understanding of the specific components of EIP care that contribute to these improvements. There is significant nationwide variability in the commissioning and delivery of EIP, with individuals receiving different packages of components from different services. In this study, we seek to explore associations between EIP components and clinically significant outcomes, in order to understand the mechanisms underlying improved psychosis care.This national retrospective cohort study will utilise data from the 2019 National Clinical Audit of Psychosis (NCAP), examining the care received by 10,560 individuals treated by EIP services in England. Exposure data from the NCAP, capturing the components of care delivered by EIP services, will be linked with outcome data from routine NHS Digital datasets over a three-year follow-up period. This will be the first study to use this method to examine this population in England. The primary outcomes will be surrogate measures of relapse of psychosis (hospital admission and referral This is a provisional file, not the final typeset article to community-based crisis intervention services). Secondary outcomes include duration of admissions, emergency hospital attendances, episodes of detention under the Mental Health Act, and all-cause mortality. We will use multilevel regression to examine associations between exposures and outcome events. We will handle missing data using appropriate imputation techniques.This study aims to provide valuable insights into the long-term effects of variations in EIP service delivery. The study involves a large, diverse cohort including individuals treated by every EIP service in England. While there are limitations inherent in the observational nature of the study, any associations identified will be of great relevance to clinicians, researchers, and policymakers seeking to optimise EIP care. The results will enable more targeted treatment planning, resource allocation, and potential innovations in EIP care, ultimately leading to improved prognoses for people experiencing psychosis.